A DIRECTIVE SPEECH ACT OF HATE SPEECH ON INDONESIAN SOCIAL MEDIA - Ubaidillah, Ubaidillah; Wijana, I Dewa Putu (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2021)
Hate speech is not only about shared knowledge but also desires and hatred. The purpose of hate speeches is to give the addressee the knowledge unknown before and make them want something never thought of and feel something. This paper describes the type of illocutionary force of hate speech on social media in Indonesia. The utterances used as data have been stipulated by the Indonesian court violating Article 28 and 45a Information and Electronic Transactions Law or article 156a Criminal Code. This article found that the illocutionary forces of hate speeches on Indonesian social media are to express incitement, invitation, order, prohibition, criticism, and warning. The illocutionary functions of these acts are at (1) addressee's compliance upon the will of the speaker; (2) dismantlement of the identity that is the source of the speaker's hatred; or (3) elimination of hatred targets.